Teacher’s Emotional Intelligence and Employee Brand-Based Equity: Mediating Role of Teaching Performance and Teacher’s Self-Efficacy - Lu, Qiaoqiao; Ishak, Nor Asniza (Frontiers in Psychology, 2022)
Educational institutions need to respond to global competitive problems, and branding has become a method for higher education institutions to differentiate themselves. Thus, this study attempted to investigate predictors of employee brand based equity. A cross sectional research design has been used to record the perception of the teachers and data is collected under convenience sampling technique. Before administrating study on large scale, a pilot testing was conducted and reliability of the scale and their items was ensured. Pilot testing results indicated a satisfactory reliability level and constructs correlations were in the assumed directions which allowed to conduct the study on large scale. A sample size of 400 was set and questionnaires were distributed among the participants, out of which 376 were received back while 351 were left at the end after discarding incomplete responses. The left over and completed questionnaires indicate88% response rate. Data has been analyzed through Smart PLS software by applying structural equation modeling technique. After establishment of measurement model through reliability and validity the structural model was used to test study hypotheses. All the study hypotheses were found statistically significant on the basis of t and p statistics. Results indicate that Teacher’s emotional intelligence enhancesteachersself-efficacy which further improves their brand based equity. Similarly, emotional intelligence increases teacher’s performance which also increases their brand based equity. Limitations and future directions of the study are also reported.